Phytochemical contents and bioactivity of nephelium lappaceum l. (rambutan) and nephelium ramboutan-ake (pulasan) - Akrimi Najihah Mohd Khamil; Teck Wei Lim; Deron R. Herr; Jualang Azlan Gansau; Siew-Eng How; Lucky Poh Wah Goh (Malaysian journal of biochemistry & molecular biology, 2025)
Fruits are the natural sources of antioxidants. In this study, we determined the total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities of various parts (peels, seeds, and pulps) of Nephelium lappaceum L. (rambutan merah and rambutan kuning) and Nephelium ramboutan-ake (pulasan). The fruit extracts were obtained by maceration with ethanol (70%) as the solvent. The TPC, TFC, and antioxidant activities were determined by FolinCiocalteu reagent, aluminum chloride colorimetric method, and 2, 2-diphenyl-1picrylhydrazyl (DPPH) radical scavenging method, respectively. The results were statistically analyzed by ANOVA and Tukey’s Honest Significant Difference (HSD) post hoc test. Overall, the fruits peel yielded the highest TPC (9.63 mg gallic acid equivalents, GAE/g on average) and TFC (740.83 mg quercetin equivalent, QE/g on average). Furthermore, the fruit peels showed the highest antioxidant activity (1.483 antioxidant activity index, AAI on average). Meanwhile, by comparing the edible pulps, Nephelium ramboutan-ake showed the highest TPC (4.33 mg GAE/g), TFC (94.31 mg QE/g), and antioxidant activity (1.17 AAI) among the fruits. In conclusion, the results suggest that the byproducts (peels and seeds) of the fruits could be potentially processed as functional foods and alternative sources of antioxidants.